Sexual knowledge, risk behavior, and access to reproductive health services among orphaned adolescents in Southwest Nigeria: implications for institutionalized care - Faramade, Ifedola Olabisi; Olugbenga-Bello, Adenike Iyanuoluwa; Goodman, Olayinka Olufisayo (Frontiers in Global Women's Health, 2023)
Introduction An orphan has been defined as a child under 18 years of age who has lost one or both parents to any cause. It has been reported that for every 10 Nigerian children, 1 is likely to be an orphan. Adolescents are faced with a serious challenge in meeting their reproductive health need, which oftentimes becomes overwhelming especially when they are orphaned. Objectives We compared institutionalized and non-institutionalized orphaned adolescents for their knowledge of sexuality, risky sexual practice, and access to reproductive health services. Methods The study adopted a cross-sectional descriptive study design conducted via structured, pretested, and interviewer-administered questionnaires among 205 orphaned adolescents (140 institutionalized and 65 non-institutionalized). Data were analyzed using the Statistical Product and Service Solution (SPSS version 25.0) and summarized using frequency, mean and percentages, and inferential statistics. All analyses were done at a 95% confidence interval and at a p < 0.05 level of significance. Results The knowledge levels of a majority of non-institutionalized respondents (73.8%) were good when compared with those in institutions (56.4%) (χ2 = 5.713, p = 0.017). Institutionalized orphans displayed better sexual behavior (80.7%) than non-institutionalized respondents (64.6%) (χ2 = 6.239, p = 0.011). Access to reproductive health services was found to be slightly higher among institutionalized respondents (66.4%) than among their non-institutionalized counterparts (64.6%). Conclusion Institutionalized and non-institutionalized orphans differed in terms of their knowledge of sexuality, sexual behavior, and risky practices, including access to reproductive health services. This study demonstrated the effectiveness of institutionalized care of orphans toward improved access to reproductive health services and good sexual practices. In the light of this, the government and relevant stakeholders should advocate the need for providing better sexuality education and understanding, make sure that access barriers for orphans are removed and orphans utilize the facilities for reproductive health that are available, and also make sure that adolescent health policies are implemented effectively.